Science vs. profit in research: Lessons from the human genome project - Carlo Carraro; Alessandra Pomè; Domenico Siniscalco (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper elaborates on the recent race to sequence the human genome. Starting from the debate on public vs. private research arising from the genome case, the paper shows that in some fundamental research areas, where knowledge externalities play an important role, market and non-market allocation mechanisms do coexist and should coexist in order to ensure socially desirable achievements. A game-theoretic model makes it possible to demonstrate the above results and to characterise some features of an optimal research policy.
Keywords: D78; H4; H23; O32; O38; 330; Science; technology; allocation mechanisms; intellectual property rights; welfare; Gentechnik; Forschung; Allokation; Immaterialgüterrechte; Wohlfahrtstheorie; Spieltheorie; Theorie